FROM ANGER TO SUBMISSION IN VICTOR HUGO’S LES CONTEMPLATIONS - Biglari, Amir (Laboratório Editorial FCL-UNESP, 2015)
This study aims to analyze two successive emotional states in Victor Hugo’s Les Contemplations: first that of anger (“Trois ans après”), followed by that of submisson (“A Villequier”). An attempt is made to apply the semiotic theory in order to elucidate the discursive characteristics of these states. Specifically, by using the canonic emotional scheme, the tensive point of view and the semiotics of instances, this analysis highlights the actantial, modal, spatial, temporal, aspectual, axiological and enunciative transformations taking place during this change. At the same time, this work intends to test the heuristic efficiency of the semiotic theory.